NanoPhytoformulations: what is so interesting about the nanoscale ? (Sciences of Phytochemistry, 2022)
Nanotechnology is on the threshold of providing a host of new materials and approaches in revolutionizing the medical and pharmaceutical fields. The incorporation of nanotechnology in herbal formulation investigation has a huge number of benefits for phytomedicine such as enhancement of solubility and bioavailability, reinforcement of pharmacological activity, improvement of stability, protection from toxicity, sustained delivery, and safeguarding from physical or chemical degradation. This opinion paper briefly highlights the authors perspective on herbal nanotechnology through few key points.